Thermodynamics problem solving in physical chemistry : study guide and map - Murphy, Kathleen E., Ph. D. (Boca Raton : CRC Press, 2020)
"This innovative and unique workbook and "map" guides physical chemistry students through the decisions to be made to assess a problem situation, create appropriate solutions, and gain confidence through practice solving physical chemistry problems. The workbook includes six major sections with 20 - 30 solved problems in each section that span from easy, single objective questions to difficult, multistep analysis problems. Each section of the workbook has "key points" that highlight major features of the topic to remind students of what they need to apply to solve problems in the topic area. Consequently, the workbook and map can act as a "test" review for the students"--
Gases and gas laws -- First law of thermodynamics -- Second and Third law of thermodynamics, [Delta]S -- Free energy ([Delta]G), Helmholtz energy ([Delta]A) and equilibrium -- Two component systems : ideal and real solutions, colligative properties -- Free energy, equilibrium constants and electrochemistry.
OCLC-licensed vendor bibliographic record.
Keywords: Thermodynamics -- Mathematics -- Problems, exercises, etc; Chemistry, Physical and theoretical -- Mathematics -- Problems, exercises, etc; SCIENCE / Chemistry / General; SCIENCE / Physics; SCIENCE / Chemistry / Physical & Theoretical